2014
DOI: 10.1155/2014/759862
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Approach by Integrating Brain Storm Optimization Algorithm with Grey Neural Network for Stock Index Forecasting

Abstract: Stock index forecasting is an important tool for both the investors and the government organizations. However, due to the inherent large volatility, high noise, and nonlinearity of the stock index, stock index forecasting has been a challenging task for a long time. This paper aims to develop a novel hybrid stock index forecasting model named BSO-GNN based on the brain storm optimization (BSO) approach and the grey neural network (GNN) model by taking full advantage of the grey model in dealing with data with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…We found that the swarm intelligence optimization methods have the potential to achieve these goals. They have been successful in the fields such as beamforming-based pattern synthesis [ 12 ], array optimization [ 13 , 14 ], DC brushless motor efficiency problems [ 15 ], Loney’s solenoid problem [ 16 ], and stock index forecasting [ 17 ]. Extensive literature reveals that compared to traditional particle swarm optimization (PSO), genetic algorithm (GA), and differential evolution (DE), the brainstorm optimization (BSO) algorithm [ 18 ] has the characteristics of fast convergence, excellent robustness, and a strong global optimization ability in solving non-convex, multi-objective, and multi-modal optimization problems.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the swarm intelligence optimization methods have the potential to achieve these goals. They have been successful in the fields such as beamforming-based pattern synthesis [ 12 ], array optimization [ 13 , 14 ], DC brushless motor efficiency problems [ 15 ], Loney’s solenoid problem [ 16 ], and stock index forecasting [ 17 ]. Extensive literature reveals that compared to traditional particle swarm optimization (PSO), genetic algorithm (GA), and differential evolution (DE), the brainstorm optimization (BSO) algorithm [ 18 ] has the characteristics of fast convergence, excellent robustness, and a strong global optimization ability in solving non-convex, multi-objective, and multi-modal optimization problems.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was proposed in 2011, BSO has been a focus of swarm intelligence research due to its novelty and efficiency. BSO has been successfully applied to various scenarios such as function optimization, engineering optimization, and financial prediction [4,[36][37][38][39]. However, as with other swarm intelligence optimization algorithms, BSO is prone to falling into local optima and premature convergence.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other intelligent optimization algorithms, BSO has the advantages of a compact mathematical model , simple operation, clear process, fast convergence speed and high optimization efficiency. Therefore, it is considered to be a very promising method, and it has been favored by many researchers and widely applied in practical optimization problems in different fields such as power systems [9], [10], [11], [12], [13], machine learning [14], [15], [16], [17], [18], [19], combinatorial optimization problems [20], [21], [22] and image processing [23], [24], [25] and prediction [15], [26], [27].…”
Section: Introductionmentioning
confidence: 99%